UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN COOKING CLASS UNTUK ANAK USIA 4-5 TAHUN DI PAUD PUTRI MUTIARA CERIA KOTA PEKANBARU - Indrawaty, Tri Putri; Zulkifli N, Zulkifli N; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study aims to investigate the influence of activities Cooking Class for Kids fine motor skills. This study consists of two variables: fine motor and cooking class. The hypothesis proposed in this study are as follows: Through the implementation of this cooking class activities can improve fine motor skills of children aged 4-5 years in early childhood Cheerful Pearl Pekanbaru City ". The study involved 15 children sabjek namely early childhood Cheerful Pearl age 4-5 years. Methods of data collection in this study using observation. The data analysis technique used in this study is a partial correlation techniques with the help of SPSS 16.0 for facilities windos. The results showed there was a significant positive correlation between the activities Cooking Class with fine motor fine motor skills a child has always increased in each cycle. It can be seen from figures ranging from pre-acquisition cycle to the second cycle. Where the scoring average of 34.00% pre-cycle, the first cycle of 44.67%, and the second cycle figures obtained an average of 66.11%.Keywords: Motor Fine, Cooking Class